Optimization of Business English Teaching Based on the Integration of Interactive Virtual Reality Genetic Algorithm - Xiao Ma (Journal of Electrical and Computer Engineering)
With the continuous advancement of the global economy and the deepening of internationalization and openness, it is also necessary to keep pace with the times in the optimization of business English teaching. At this point, a genetic algorithm based on the interactive virtual reality (VR) should be established for the optimization of business English teaching to adapt to the future trend in business English teaching optimization more appropriately. In the business English teaching process at present, it is required to change the traditional teaching concept, adjust the previous teaching ideas, widen the horizon continuously, establish an international and diversified English teaching and training program, incorporate the outstanding foreign teaching models, and proactively absorb the excellent educational concepts to drive the development of the domestic business English teaching model more effectively. The results of the simulation experiment indicate that the improved algorithm designed in this article can reduce the computational overhead of the meta-algorithm to a great extent, and the improvement strategy is designed based on the evaluation results of practical examples.